2009
DOI: 10.1002/hlca.200800289
|View full text |Cite
|
Sign up to set email alerts
|

A New Sesquiterpene from Ximenia americanaLinn.

Abstract: The new sesquiterpene 1, named ximonicane, and the known stigmastane steroid 2 were isolated from the EtOH extract of the stems of Ximenia americana. Spectroscopic methods, including 2D-NMR techniques, have been used to characterize 1 and assign all the signals of the 1 H-and 13 C-NMR spectra of 1. Ximonicane did not inhibit the growth of HL-60 (human leukemia), HTC-8 (human colon), and MDA-MB-435 (human breast cancer) cell lines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 4 publications
(3 reference statements)
0
5
0
Order By: Relevance
“…The (James et al, 2007& Ogunleye et al, 2003; few extracts showed also the presence of cyanogenetic glycosides (Ogunleye et al, 2003). Quinones are of the anthraquinone type; terpenes are sesquiterpenes and triterpenes type (Araújo et al, 2008(Araújo et al, , 2009 The methanolic extract was the most active one. The aqueous extract also exhibited high activity which justifies its traditional use.…”
Section: Antimicrobial and Antifungal Activitiesmentioning
confidence: 99%
See 2 more Smart Citations
“…The (James et al, 2007& Ogunleye et al, 2003; few extracts showed also the presence of cyanogenetic glycosides (Ogunleye et al, 2003). Quinones are of the anthraquinone type; terpenes are sesquiterpenes and triterpenes type (Araújo et al, 2008(Araújo et al, , 2009 The methanolic extract was the most active one. The aqueous extract also exhibited high activity which justifies its traditional use.…”
Section: Antimicrobial and Antifungal Activitiesmentioning
confidence: 99%
“…In this context it is important to point out that the norisoprenoid isophorane (10), shown to be carcinogenic agent (Mevy et al, 2006), was identified in the leaves of X. americana, which would conflict with its use in treating cancer. The last report about compounds isolated from X. americana up to date were the sesquiternes 7 and 8, triterpenoids 18-22 and steroids 24-26, all from ethanol extract of stems (Araújo et al, 2008(Araújo et al, , 2009). Some of them have not yet been exhaustively investigated from the point of view of biological activity.…”
Section: Food Composition and Cosmetic Usementioning
confidence: 99%
See 1 more Smart Citation
“…397 Ximonicane 444 is a new sesquiterpene from the bark of Ximenia americana. 398 The absolute configurations of (+)-echinopines A and B 399 and of a b-farnesene-trimethoxystyrene conjugate 400 have been determined by chemical synthesis. An enantioselective total synthesis of ent-10,11-epoxythapsan-10-ol has been achieved.…”
Section: Miscellaneous Sesquiterpenoidsmentioning
confidence: 99%
“…Sambunigrin was isolated from the leaves in 1938 (Finnemore and Cooper, 1938). In recent years, fatty acids, volatile oil constituents, sesquiterpenes, triterpenes and phytosterols are reported from the seeds, leaves and stems (Eromosele and Eromosele, 2002;Mevy et al, 2006;de Araújo et al, 2008de Araújo et al, , 2009. The chemistry of the roots is still unknown.…”
Section: Introductionmentioning
confidence: 97%